Velvet bean (Mucuna pruriens) meal as a substitute for soybean cake and its effect on the productive performance of broilers - Celis del Águila, William (2020)
The aim of this study was to determine the effect of velvet bean (Mucuna pruriens) meal as a partial substitute for soybean cake on the productive performance of broiler chickens in the finishing phase. The study included 336 21-day-old Cobb chickens in four treatments with three replications: T0=0%, T1=5%, T2=10%, and T3=15% soybean cake replacement with velvet bean. The feed consumption of T2 and T3 chicks was significantly lower than in the control group (p<0.05), but similar to T1. Feed conversion was similar between the three velvet bean treatments, but T2 presented a better conversion than T0 (p<0.05). Carcass percent and body weight gain were similar among treatments. The highest economic returns were obtained in T2 (S/. 1.75 per chicken) and T0 (S/. 1.73), closely followed by the other treatments. It is concluded that 10% velvet bean meal can be used in the feed ration without affecting the productive performance.